Heavy metal (iron) removal from landfill eachate by using two-stage constructed wetlands planted with Limnocharis flava and Eichhornia crassipes - Ain Nihla, Kamarudzaman; Johan, S.; Roslaili, Abdul Aziz; Wong, Yee Shian; Mohd Faizal, A. J. (Universiti Malaysia Sarawak (UNIMAS), 2011)
3rd Regional Conference on Natural Resources in the Tropics (NRTrop3_2009) organized by Faculty of Resource Science & Technology, Universiti Malaysia Sarawak, from 3rd - 5th August 2009 at Kuching, Sarawak, Malaysia.